Análise dos serviços de assistência farmacêutica nos municípios da 27ª região de saúde do Rio Grande do Sul - Silveira, Taíse Foletto (2023)
Pharmaceutical Services (PS) involves a set of steps aimed at maintaining access to medicines and promoting rationality of use. Its services include managerial activities, with a logistical focus, and clinical activities, which include education actions with the health team and the community, in addition to direct care provided to patients. The actions must be integrated with each other and articulated with other health services. This study aimed to analyze the execution of PS actions in the twelve municipalities of the 27th Health Region of Rio Grande do Sul and, through the perception of key actors, characterize the management and structuring of PS, in addition to understanding the challenges and advances for consolidating management and clinical services. A cross-sectional study was conducted in which the source of information was professionals and managers of the Brazilian public health system (SUS) at the municipal level. Data collection occurred from June to December 2021, through individual remote interviews, with the application of semistructured questionnaires. The data were analyzed quantitatively, based on absolute and relative frequencies, and quali-quantitative, using the Collective Subject Discourse technique. The results pointed to a heterogeneous reality, some municipalities stood out positively, because the pharmacist is involved in the elaboration of management instruments, there is integration of this professional with collaborative activities in Primary Health Care and pharmaceutical care activities are offered. According to the reports of pharmacists who perform individual care and other evidence in the literature, through this activity it is possible to detect problems associated with the use of pharmacotherapy, so the absence of clinical services leads to ignorance of such failures. Despite advances, rapid delivery of medicines is a reality in some places. Ensuring access is essential for the SUS, however, only the availability of the drug is insufficient for Rational Drug Use (RDU), so pharmaceutical services should be recognized as part of the care process. The challenges that compromise the promotion of RDU include the shortage of professionals working in PS, inadequate ambience, insufficient training and the vision of professionals, managers and users focused on medicine. Municipalities also face budget deficits that require more efficient management of health resources. It is concluded that the reorganization of pharmaceutical services raises the recognition of existing barriers, which serves as an incentive for managers and for the articulation of pharmacists in other health services and in the planning of actions.